ENGLISH LANGUAGE TEACHING AT MAKASSAR PRIMARY SCHOOLS: A CASE STUDY - Rosmaladewi, Rosmaladewi (Universitas Negeri Makassar, 2017)
The research aims to describe current practice of English as a foreign language at primary schools. The case study conducted at two favorite elementary schools in Makassar involving 84 students. The data gained through observation, questionnaire and semi-structured interviews.Â The study revealed that teachers used textbook as the main resources for teaching besides using media and physical objects. The research identifies that there are a lot of challenges faced by both teachers and students in teaching and learning English. From teachersâ€™ perspective, the difficulties are limited availability of materials, allocation of time, class size, and using teaching media. Students preferred variety of teaching method as well as materials.Â From the learners viewed that time allocation is not enough, and teaching material are not varied. It is suggested that the government should provide a variety of teaching materials that can assist teachers and students in teaching and learning English